Điều trị ung thư trực tràng bằng phẫu thuật nội soi một lỗ (Single Port) - Hiệp, Phạm Như; Thiện, Hồ Hữu; Vũ, Phạm Anh; Thanh, Phan Hải; Điềm, Trần Sĩ Doãn; Xuân, Nguyễn Thanh; Trung, Trần Nghiêm; Vĩ, Phạm Trung; Đông, Phạm Xuân; Đức, Phạm Minh; Hiếu, Mai Trung (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
A